DOMINO INTERACTIVE IN THEORETICAL MECHANICS LECTURES APPLY THE METHOD (Innovative Technologica: Methodical Research Journal, 2021)
This article discusses the possibilities of using the domino method, which is one of the interactive methods in teaching theoretical mechanics. The application of the method to a specific subject of science is given.